Contracts Relating To Marriage - Sinnadurai, Visu (Journal of Malaysian and Comparative Law, 1979)
The purpose of this paper is to make a study of Malaysian cases on certain contracts relating to marriage: marriage brocage, restraint of marriage and promises by married persons to marry another. A common feature of the contracts under study is that they are rendered void under the common law. The reason attributed for so rendering it void is that such contracts are against public policy. It is proposed in this paper to make a comparative study of these three types of contracts both under the common law and under Malaysian law. A study will also be made to determine whether the reasons for not enforcing these contracts under the common law are also applicable in Malaysia. The paper will be divided into two part: Part I deals with marriage brocage agreements, whilst Part II deals with restraint of marriage and promises made by married persons. The consequences of such agreements will also be dealt with in Part II.